2012
DOI: 10.1371/journal.pone.0037443
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Caspase 9 Polymorphisms in Promoter and Exon Sequence on Cancer Susceptibility

Abstract: BackgroundCaspases are important regulators and executioners in apoptosis pathway and have been defined as either tumor suppressors or oncogenes. Polymorphisms in promoter and exon of caspase 9 were shown to confer genetic susceptibility to multiple cancers, but the results were inconsistent. To accomplish a more precise estimation of the relationship, a meta-analysis was performed.Methodology/Principal FindingsWe assessed published studies of the association between caspase 9 polymorphisms and cancer risk fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
14
2
Order By: Relevance
“…In contrast, carriers of CASP9 c.‐1339AA genotype were under increased risk of the lung, bladder, gastric, prostate, and colorectal cancer, and reduced risk of pancreatic and breast cancer. Most of the studies mentioned above were included in a meta‐analysis that showed no association of CASP9 c.‐1339A>G and risk of various types of cancer, giving support to our data.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, carriers of CASP9 c.‐1339AA genotype were under increased risk of the lung, bladder, gastric, prostate, and colorectal cancer, and reduced risk of pancreatic and breast cancer. Most of the studies mentioned above were included in a meta‐analysis that showed no association of CASP9 c.‐1339A>G and risk of various types of cancer, giving support to our data.…”
Section: Discussionsupporting
confidence: 84%
“…One important property of CASP9 gene polymorphisms is that the incidence can differ substantially among different populations. Their data demonstrated significant differecences in the prevalence of the CASP9 allele between Caucasion and Asians populations (11).…”
Section: Discussionmentioning
confidence: 94%
“…Current researches show that genetic polymorphisms can explain and contribute to inter-individual differences in oncogenesis and differentiation (Kutikhin 2011;Gu et al, 2012;Nakada et al, 2012;Xu et al, 2012). In 2011, Wei et al (2011).…”
Section: Introductionmentioning
confidence: 99%